Evaluating attachment-based family therapy in residential treatment in the United States: does adolescents’ increased attachment security to caregivers lead to decreases in depressive symptoms? - Guy Diamond; Alannah Shelby Rivers; Payne Winston-Lindeboom; Jody Russon; Michael Roeske (Child and Adolescent Psychiatry and Mental Health)
Abstract Background The inclusion of family therapy in residential treatment centers (RTCs) has increased over time. However, there is little data on whether empirically-supported family therapies (ESFTs) are being adopted and if they contribute to treatment effectiveness. This study aimed to test whether Attachment-Based Family Therapy (ABFT), an ESFT integrated into a large residential psychiatric system, would improve perceived attachment insecurity (anxiety and avoidance) and contribute to decreases in depression for adolescents. Method ABFT was integrated into the clinical program of a large, residential psychiatric system. All family therapists were trained to a level of certification. Improvement was measured by changes in adolescent’s perceived attachment to caregivers and reduction in depressive symptoms. The sample included 4786 patients. Attachment insecurity and depressive symptoms were measured at intake, week 3, and week 5. A random-intercept, cross-lagged panel model was used to examine the relationships between attachment and depression over time. Results The results generally supported hypotheses. Attachment insecurity and depressive symptoms improved over the five weeks of treatment. Improvements in attachment avoidance preceded improvements in depressive symptoms within subjects, over time. Simultaneously, improvements in depressive symptoms preceded those in both dimensions of attachment. Thus, improvement in perceived attachment was associated with a reduction in depressive symptoms. Conclusion RTCs that can generate improvements in attachment insecurity and depressive symptoms, via ABFT or other ESFTs, might improve treatment outcomes, and ideally, adolescents’ successful transition back home to families. More research is needed to disentangle the contribution of ABFT and other treatment elements in a multimodal, residential treatment program. The study supports the call for increased incorporation of families into the RTC treatment process.